Socioeconomic status and trends in utilization of catheter ablation in patients hospitalized with atrial fibrillation in united states. (14th October 2021) - Rojulpote, C; Patil, S; Gonuguntla, K; Kharbanda, P; Karambelkar, P; Kela, K; Singh, V; Nadadur, S; Kumar, M; Buch, T
Abstract: Introduction: Atrial fibrillation (AF) is the most common arrhythmia encountered in a hospital setting. However, there is little data on the relationship of socioeconomic status (SES) and the utilization of catheter ablation amongst patients admitted with AF. Methods: The National Inpatient Sample database was queried from 2003 to 2014 using ICD 9 revised diagnosis codes to identify patients who were hospitalized with a primary diagnosis of AF. SES was determined by median household income (MHI) and divided into quartiles (0–25th, 26–50th, 51–75th, and 76–100th). Trends were analyzed using Cochran Armitage test. Results: We analyzed 3, 618, 133 patients with AF that were admitted from 2003 to 2014 (median age: 72 [IQR 61 – 81], female 52.6%). Trends stratified by MHI to compare catheter ablation rates of all 12 years revealed significant differences (Figure 1). A multivariable logistic regression accounting for sociodemographic factors revealed an increasing trend of catheter ablation utilization with higher MHI (Figure 1). Conclusion: Over a 12-year period, patients admitted to the hospital with AF with higher MHI were found to have increasing rates of catheter ablation utilization due to AF. Conversely, a decline in catheter ablation rates were noted in patients with lower MHI. Funding Acknowledgement: Type of funding sources: None.